Unexpected benefit of a social parasite for a key fitness component of its ant host. - Hovestadt, T; Thomas, J; Mitesser, O; Elmes, G; Schönrogge, K (2012)
Numerous invertebrates inhabit social insect colonies, including the hoverfly genus Microdon, whose larvae typically live as brood predators. Formica lemani ant colonies apparently endure Microdon mutabilis infections over several years, despite losing a considerable fraction of young, and may even produce more gynes. We present a model for resource allocation within polygynous ant colonies, which assumes that whether an ant larva switches development into a worker or a gyne depends on the quantity of food received randomly from workers. Accordingly, Microdon predation promotes gyne development by increasing resource availability for surviving broods. Several model predictions are supported by empirical data. (i) Uninfected colonies seldom produce gynes. (ii) Infected colonies experience a short-lived peak in gyne production leading to a bimodal distribution in gyne production. (iii) Low brood : worker ratio is the critical mechanism controlling gyne production. (iv) Brood : worker ratio reduction must be substantial for increased gyne production to become noticeable.